Perancangan Dan Pembuatan Ackerman Mobile Robot Dengan Kendali Pid Untuk Menghindari Halangan Berbasis Hybrid System - Kesuma Dewi, Ratih; Widyantara, Helmy; Christrian W., Madha (Journal JCONES, 2012)
Robot is a key driver of modern industry, it is a symbol of technological progress in the 21st century. With the robots can alleviate human work because robots have the advantage over men, among others, in terms of speed, accuracy, and most importantly, are able to perform dangerous work that humans can not be done directly, for example, data collection in the area of the volcano and clean up spills radioactive. It required a robot that has the ability to avoid obstacles (obstacle avoidance) in order to achieve the mission of a robot. So that the robot can walk with subtle needed a controller, which is used to control system with PID control parameters are input using proximity sensors (position sensitive device). The proximity sensor is a sensor types in the form of an analog voltage output. It required an analog processor, one is the FPAA. FPAA is an integrated circuit that can be configured to create multiple analog functions using multiple CAB (Configurable Analog Blocks) and interconection CAB network to connect between each other and are equipped with input - output (I / O) block and memory storage media type of RAM (Read Access Memory). In this study, the sensor output is used FPAA with PID control to adjust the speed of the motor. To avoid bumping into obstacles added a proximity sensor on the left and right front. However, in this study the PID controller as expected yet. Keyword: Robot, PID, dan FPAA